Placental Circulation Intact Trial (PCI-T)—Resuscitation With the Placental Circulation Intact vs. Cord Milking for Very Preterm Infants: A Feasibility Study - Pratesi, Simone; Montano, Simona; Ghirardello, Stefano; Mosca, Fabio; Boni, Luca; Tofani, Lorenzo; Dani, Carlo (Frontiers in Pediatrics, 2018)
Background Preterm newborns receiving briefly delayed cord clamping or cord milking at birth have better neonatal outcomes. However, the time frame in which both these procedures are performed (<60 s of life) is too short to explore the possible beneficial effects on early infant postnatal adaptation and outcomes of a prolonged transfusion strategy associated with neonatal respiration. Methods/Design We have designed a randomized, multicenter, controlled two-phase study: phase 1 to assess the feasibility of carrying out the protocol in a large randomized trial, and phase 2 to assess the efficacy of bedside assistance with intact placental circulation for 3 min in comparison to cord milking to improve outcome in the neonatal period; we present here the feasibility and safety phase of the study. Outcomes included feasibility (recruitment rate of two patients per month, compliance with the trial interventions, completeness of data collection, >90% of infants receiving echographic assessments in the first 24 h) and safety variables (5 min Apgar score, delivery room intubation rate, CRIB II score, admission temperature, maximum hemoglobin concentration and hematocrit in the first 24 h and maximum serum bilirubin value) in the two study groups. We also evaluated the same safety variables in infants delivered during the study period but not recruited. Results A total of 40 infants were enrolled. In all cases the protocol was completed and all feasibility outcomes were reached. Infants assisted with an intact placental circulation have a higher 5 min Apgar score but their admission temperature was lower than milked infants. Delivery room intubation rate, CRIB II score and peak serum bilirubin value were comparable in both groups. Infants who were not subjected to a placental transfusion strategy (excluded patients) had a higher delivery room intubation rate with respect to both study groups. Conclusion Delaying cord clamping until 3 min of life was challenging but feasible and appeared to be safe. However, admission temperature must be strictly monitored and a more efficacious warming system could be implemented to prevent hypothermia during the procedure.